Prospects of longan cultivation in India - Kumar, Sunil; Kumar, Abhay; Pandey, Sheshdhar; Dhakar, Mahesh Kumar (Indian Horticulture, 2022)
Longan is an exotic, subtropical, delicious fruit with sweet and juicy pulp. A recent understanding of its medicinal and health properties has led to the expansion of production areas of longan in different countries. In India, it is grown on a limited scale in Bihar, Jharkhand and West Bengal and has gained much attention in the recent years. Increasing production of longan fruit raises prospects for further utilization of this crop in India.